Index membership vs. loss of voting power: The unification of dual-class shares - André Betzer; Inga van den Bongard; Marc Goergen (University of Wuppertal, Schumpeter School of Business and Economics, 2017)
A change in the index selection rules of Deutsche Börse provides a unique opportunity to investigate the drivers behind the decision to a bolish dual-class shares. As of June 2002, selection is based on the market capitalization of the free-float of the more liquid share class rather than the overall market capitalization. Hence, firms have had to reassess the benefits from their dual-class shares by weighing them against the cost from foregone index weight associated with having two share classes. Our findings suggest that index membership significantly affects the controlling shareholder's motivation to unify preferred and common stock.
urn:nbn:de:hbz:468-20170413-131411-4
Keywords: G30; G32; 330; private benefits of control; dual-class stock; ownership structure; corporate governance